The effect of debt to equity ratio and company size on profit growth in property and real estate sub-sector companies listed on the Indonesia Stock Exchange for the 2020-2022 period - Supyati, Supyati; Fadillah, Siti Azzah; Nahrumi, Arum; Haryadi, Didit (International Journal of Applied Finance and Business Studies, 2024)
This study investigates the interaction of debt-to-equity ratio, company size, and corporate profit on companies in Indonesia's property sector. The aim is to gain insight into how these factors interact and affect the overall value of a company's earnings in a particular property sector area. This analysis uses quantitative methods based on financial data and relevant metrics for a sample of manufacturing companies operating in Indonesia, as many as 23 companies. This study examines the relationship between debt-to-equity ratio, company size, and company profit through statistical analysis and linear regression modeling techniques with SPSS version 26. The results showed that the debt-to-equity ratio did not affect the company's profit; the size of the company had a significant effect on the company's profit. The debt-to-equity ratio and the company's size do not impact the company's profit. The findings contribute to the existing literature on company valuations by providing empirical evidence specific to the property sector. The research has implications for policymakers, investors, and managers, as it offers valuable insights into the factors that drive a company's profit value, helping stakeholders make decisions and strategies to improve performance and competitiveness. Provide benefits in the context of financial management